Concomitant administration of a fully liquid, ready-to-use DTaP-IPV-HB-PRP-T hexavalent vaccine with a meningococcal serogroup C conjugate vaccine in infants. Issue 3 (11th January 2017) - Vesikari, Timo; Borrow, Ray; Da Costa, Xavier; Richard, Patrick; Eymin, Cécile; Boisnard, Florence; Lockhart, Stephen
Highlights: DTaP-IPV-HB-PRP-T immunogenicity is similar when given concomitantly with a meningococcal C conjugate vaccine or alone. The safety profile of DTaP-IPV-HB-PRP-T is similar when given concomitantly with a meningococcal C conjugate vaccine or alone. These data support the concomitant use of DTa-IPV-HB-PRP-T vaccine with a meningococcal C conjugate vaccine. Abstract: DTaP-IPV-HB-PRP-T or hexavalent vaccines are indicated for primary and booster vaccination of infants and toddlers against diphtheria, tetanus, pertussis, hepatitis B, poliomyelitis and invasive diseases caused by Haemophilus influenzae type b (Hib). The present study evaluates the safety and immunogenicity of a ready-to-use hexavalent vaccine when co-administered with a meningococcal serogroup C conjugate (MenC) vaccine in infants. This was a phase III, open-label, randomised, multicentre study conducted in Finland. Healthy infants, aged 46–74 days (n = 350), were randomised in a ratio of 1:1 to receive DTaP-IPV-HB-PRP-T vaccine at two, three and four months, either with a MenC vaccine co-administered at two and four months (Group 1; n = 175) or without MenC vaccine (Group 2; n = 175). All infants also received routine rotavirus and 13-valent pneumococcal conjugate vaccines. The proportion of participants with an anti-HBs concentration ⩾10 mIU/mL assessed one month after the third dose of DTaP-IPV-HB-PRP-T vaccine was 97.5% [95%CI: 93.1–99.3] in the coadministration group and 96.1% [95%CI: 91.8–98.6] in the group without MenC vaccine. The proportion of participants with an anti-MenC SBA titre ⩾8 assessed one month after the second dose of MenC vaccine was 100% in the coadministration group. Both primary objectives were achieved. Secondary immunogenicity and safety analyses showed that co-administration of DTaP-IPV-HB-PRP-T and MenC vaccines did not impact the immune response to the antigens of each of the two vaccines. All vaccines were well tolerated and the safety profile of DTaP-IPV-HB-PRP-T vaccine was similar in both groups. ClinicalTrials.gov identifier:NCT01839175 ; EudraCT number: 2012-005547-24.